Modern Broods; Or, Developments Unlooked For - Yonge, Charlotte M. (Charlotte Mary), 1823-1901 (Salt Lake City, UT : Project Gutenberg, 2004)
"Modern Broods; Or, Developments Unlooked For" by Charlotte M. Yonge is a novel likely written in the late 19th century. The story revolves around the life of Magdalen Prescott, who comes into an unexpected inheritance and seeks to establish a home for her younger sisters, Agatha, Vera, and Paulina, while navigating the challenges of family dynamics and societal expectations. At the start of the novel, we meet Magdalen as she greets her friend Mrs. Best and learns of her inheritance$1 (Ba modest house in Devonshire along with financial support. The opening chapters introduce the sisters, who come from a close yet complicated relationship with their new sister figure, and hint at the personalities and aspirations of each character. The sisters express excitement and trepidation about their new life, eager to explore their new surroundings while also grappling with their transitions from childhood to maturity. As relationships are forged and tested, readers are drawn into themes of family loyalty, personal ambition, and the quest for individual identity in a changing world. (This is an automatically generated summary.)s
Release date is 2004-12-01
Transcribed from the 1900 Macmillan and Co. edition by David Price
Keywords: England -- Social life and customs -- 19th century -- Fiction; English fiction; Domestic fiction